Financing Structure of Enterprises in the Metal Industry in Poland Between 2000 and 2010 - Piotr Rzeszowski; Maria Sierpińska (Contemporary Economics, 2012)
This paper presents research results regarding the direction of changes in financing structure adopted by enterprises in the metal industry in Poland. This sector of industry is extremely important in Poland. The main reason for undertaking this research was a desire to gain insight into the problems that enterprises experience in finding financing sources during economic crises because banks restrict lending, profit declines, and the ability to utilize capital derived from stock exchanges is limited. The assessment was based on an analysis of the structure of financing sources and the relationship of credits to own capital and to liabilities. The structure of financing sources adopted by companies in the metal industry underwent significant changes between 2000 and 2010. Enterprises in this industry began to utilize own capital more often during the period, while the proportion of external capital to total liabilities decreased. The increase in the proportion of internal capital influenced the improvement in financial liquidity but also contributed to an increase in the average cost of capital and limited the range of profitable investments. The results validate initial research hypotheses regarding an increase in the participation of internal capital in the financing of enterprises' activities and a decrease in the amount of bank loans utilized by the companies.
Keywords: G00; 330; financing structure; selection of financing sources; financial crisis